Metadata services on the Grid - Santos, Nuno (2006)
We present an interface for metadata access on the Grid, designed to support flexible schema management, efficient retrieval of large result sets and to allow a broad range of implementations. We also describe an implementation of this interface, which supports a wide range of storage back-ends and two access protocols: SOAP and a TCP-streaming-based protocol. This interface and implementation have been selected as the official metadata components of the gLite-EGEE middleware. Finally, we present the results of extensive performance studies, where the two front-ends are compared to evaluate the cost of using SOAP as metadata access protocol.